Mengurai Framing Isu dan Hyper-Asabiyya: Studi tentang Polarisasi dan Konflik di Wamena - Imroatil Aziyzil Awwalin (AL-Ikhtiar : Jurnal Studi Islam, 2025)
Recurring social conflicts in Wamena, Papua such as the violent incident in February 2023 demonstrate how narratives spread on social media can trigger collective emotional mobilization that leads to violence. This study aims to understand the social construction of the conflict by combining two main theoretical approaches: Robert Benford and David A. Snow's framing theory and Akbar S. Ahmed's concept of hyper-asabiyya. Framing theory explains how social actors shape perceptions of issues through diagnostic, prognostic and motivational framing. Meanwhile, the concept of hyper-asabiyya describes how extreme collective solidarity can emerge as a response to threats to identity and the absence of the state. The research question raised in this study is how the framing of the child abduction issue in the context of Wamena triggered collective violence and how excessive ethnic solidarity (hyper-asabiyya) played a role in the dynamics of the conflict. Through a qualitative approach with narrative and symbolic analysis, it was found that narratives of child abduction shape perceptions of threats to the existence of local communities, which are then mobilized into acts of violence. Ethnic solidarity develops into a tool for collective violence when the state fails to provide fair protection. This study highlights the importance of understanding social conflict not only from a structural perspective but also from symbolic and emotional dimensions, and offers critical reflections on the role of the media, the state, and collective identity in contemporary conflicts in Papua. Abstrak Konflik sosial yang berulang di Wamena, Papua seperti insiden kekerasan pada Februari 2023 memperlihatkan bagaimana narasi yang tersebar di media sosial dapat memicu mobilisasi emosi kolektif yang berujung pada kekerasan. Penelitian ini bertujuan untuk memahami konstruksi sosial konflik tersebut dengan memadukan dua pendekatan teoritis utama yaitu teori framing dari Robert Benford dan David A. Snow serta konsep hyper-asabiyya dari Akbar S. Ahmed. Teori framing menjelaskan bagaimana aktor sosial membentuk persepsi atas isu melalui diagnostic, prognostic dan motivational framing. Sementara konsep hyper-asabiyya menguraikan bagaimana solidaritas kolektif yang ekstrem dapat muncul sebagai respons terhadap ancaman identitas dan ketiadaan negara. Rumusan masalah yang diangkat dalam penelitian ini ialah bagaimana framing isu penculikan anak dalam konteks Wamena memicu kekerasan kolektif dan bagaimana solidaritas etnis yang berlebihan (hyper-asabiyya) berperan dalam dinamika konflik tersebut? Melalui pendekatan kualitatif dengan analisis naratif dan simbolik ditemukan bahwa narasi penculikan anak membentuk persepsi ancaman terhadap eksistensi komunitas lokal yang kemudian dimobilisasi menjadi aksi kekerasan. Solidaritas etnis berkembang menjadi alat kekerasan kolektif ketika negara gagal menyediakan perlindungan yang adil. Studi ini menyoroti pentingnya memahami konflik sosial tidak hanya dari aspek struktural tetapi juga dari dimensi simbolik dan emosional serta menawarkan refleksi kritis atas peran media, negara dan identitas kolektif dalam konflik kontemporer di Papua.